In vitro anthelmintic effect of the extract of Albizia lophantha on gastrointestinal nematodes of horses - Chicaiza-Tisalema, E. (2016)
The Albizia lophantha extract (T1: 0 mg of extract/ml of nutritive cultivation [mg/ml], T2: 0.04 mg/ml, T3: 0.08 mg/ml, T4: 0.12 mg/ml) was used to evaluate the in vitro anthelmintic effect on gastrointestinal nematodes of horses. Higher inhibition in the hatching of eggs (T4: 43% and T3: 11%, respectively) and lower in the survival of larvae in the treatments of high doses (T4: 0% and T3: 0% at 36 and 60 hours after applying the extract respectively) (p=0.0001). The A. lophantha extract was effective in the in vitro control of gastrointestinal nematodes of horses.